2017
DOI: 10.21037/jtd.2017.06.92
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve injury after esophagectomy for esophageal cancer: incidence, management, and impact on short- and long-term outcomes

Abstract: Background: Recurrent laryngeal nerve (RLN) injury caused by esophagectomy may lead to postoperative morbidity, however data on long-term recovery are scarce. The aim of this study was to evaluate the consequences of RLN palsy (RLNP) in terms of pulmonary morbidity and long-term functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 44 publications
2
46
2
Order By: Relevance
“…The recurrent laryngeal nerve palsy was not related to postoperative pneumonia and aspiration (data not shown). The previous studies reported that recurrent laryngeal nerve palsy is the risk of pneumonia and aspiration [27,28]. In the present study, the prevalence of the recurrent laryngeal nerve palsy was low.…”
Section: Discussioncontrasting
confidence: 43%
“…The recurrent laryngeal nerve palsy was not related to postoperative pneumonia and aspiration (data not shown). The previous studies reported that recurrent laryngeal nerve palsy is the risk of pneumonia and aspiration [27,28]. In the present study, the prevalence of the recurrent laryngeal nerve palsy was low.…”
Section: Discussioncontrasting
confidence: 43%
“…One possible explanation for the reduced number pulmonary complications in our series was the rate of neck anastomosis, for which a constantly higher rate of recurrent laryngeal nerve trauma has been reported (31). In the open era, this injury was related to the increased incidence of pulmonary complications, length of ventilator time, and ICU stay (32). The second reason, despite having older and comorbid patients, could be an enhanced mobilization program (33).…”
Section: Discussionmentioning
confidence: 84%
“…The technically challenging area of mediastinal nodal clearance lies in the removal of nodes along the RLN's. Where the overall incidence of RLN palsy, especially after McKeown's oesophagectomy varies from 0% to 58%,[19] reports suggest clearing lymph nodes from RLNs is necessary for better survival for SCC of midoesophagus. [20] However, with the introduction of minimally invasive techniques, this frequency is drastically reduced.…”
Section: Discussionmentioning
confidence: 99%